Effect of chiglitazar and sitagliptin on glucose variations, insulin resistance and inflammatory-related biomarkers in untreated patients with type 2 diabetes. (January 2022) - Wang, Yuming; Li, Huiqin; Gao, Hui; Xu, Xiaohua; Cai, Tingting; Wang, Huiying; Zhou, Yunting; Huang, Rong; Su, Xiaofei; Ma, Jiahuan
Abstract: Aims: To evaluate glycemic variations, changes in insulin resistance and oxidative stress after chiglitazar or sitagliptin treatment in untreated patients with type 2 diabetes mellitus (T2DM). Methods: Based on the study inclusion and exclusion criteria, 81 patients with T2DM were randomly divided to receive chiglitazar or sitagliptin treatment for 24 weeks. Continuous glucose monitoring (CGM) systems were conducted for 72 h in eligible patients. We analyzed the following glycemic variation parameters derived from the CGM data and measured the serum levels of hemoglobin A1c (HbA1c), fasting blood glucose (FBG), 2-h postprandial blood glucose (2-h PBG), fasting insulin (Fins) and inflammatory-related indicators at baseline and the end of the study. Results: After treatment for 24 weeks, our data showed a similar reduction in HbA1c between chiglitazar and sitagliptin. The 24-h mean blood glucose (MBG), standard deviation (SD) and mean amplitude of glycemic excursion (MAGE) were significantly decreased, and the time in range (TIR) was increased after chiglitazar and sitagliptin therapy. Chiglitazar administration led to significant improvement in insulin resistance/insulin secretion (HOMA-IR, HOMA-IS), interleukin-6 (IL-6), prostaglandin F2α (PGF-2α), 17-hydroxyprogesterone (17-OHP) and adiponectin (ADP) score values compared with sitagliptin administration. Conclusions: Chiglitazar therapy effectively reduced glucose variation and showed a larger improvement in insulin resistance and inflammatory parameters than sitagliptin.